Body mass index of married Bangladeshi women: trends and association with socio-demographic factors - Hossain, M.G.; Bharati, P.; Aik, S.; Lestrel, P.E.; Abeer, A.; Kamarul, Tunku (Cambridge University Press, 2012)
SummaryBody mass index (BMI) is a good indicator of nutritional status in a population. In underdeveloped countries like Bangladesh, this indicator provides a method that can assist intervention to help eradicate many preventable diseases. This study aimed to report on changes in the BMI of married Bangladeshi women who were born in the past three decades and its association with socio-demographic factors. Data for 10,115 married and currently non-pregnant Bangladeshi women were extracted from the 2007 Bangladesh Demographic and Health Survey (BDHS). The age range of the sample was 15-49 years. The mean BMI was 20.85Â±3.66 kg/m2, and a decreasing tendency in BMI was found among birth year cohorts from 1972 to 1992. It was found that the proportion of underweight females has been increasing in those born during the last 20 years of the study period (1972 to 1992). Body mass index increased with increasing age, education level of the woman and her husband, wealth index, age at first marriage and age at first delivery, and decreased with increasing number of ever-born children. Lower BMI was especially pronounced among women who were living in rural areas, non-Muslims, employed women, women not living with their husbands (separated) or those who had delivered at home or non-Caesarean delivery.